The Role of Stimulus Novelty on Children's Inflexible Dimensional Switching. Issue 4 (10th January 2014) - Jowkar‐Baniani, Gelareh; Schmuckler, Mark A.
<x xml:space="preserve">Abstract</x> Children's ability to flexibly shift attention between different representational schemes was investigated using the dimensional change card sorting task. Across three experiments (N = 56 three‐year‐olds and N = 40 four‐year‐olds in ; N = 14 three‐year‐olds in ; and N = 14 three‐year‐olds in ) the role of perceptual information on children's cognitive flexibility was investigated by manipulating different aspects of the task materials between pre‐ and postswitch phases. Better performance was observed when either task‐relevant (the color or shape of the images on the cards) or task‐irrelevant information (the background color or shape of the actual cards) was changed, with this improvement occurring when the changes were salient enough to induce a stimulus novelty effect.